Environmental protection tax law and total factor productivity of listed firms: promotion or inhibition? - Yang, Shuwang; Wang, Chao; Lyu, Kangni; Li, Jiapeng (Frontiers in Environmental Science, 2023)
The trade-off between environment and economy has been one of the hot topics discussed in academia, but there are many disputes among them. Based on a Chinese micro sample from 2016-2020, this paper uses the shock of the Environmental Protection Tax Law (EPTL) in 2018 as a quasi-natural experiment. Our Differences-in-Differences (DID) method is used to study the impact of the environmental governance pressure caused by the EPTL on firms’ total factor productivity (TFP). The conclusions suggest that: (1) The EPTL has significantly improved heavily polluting enterprises’ TFP, and this finding remains stable after a range of robustness checks. (2) The subgroup analysis shows that. The smaller the size of the administrative expenses paid by the enterprises, the larger the effect of the EPTL on firms’ TFP; the positive effect of the EPTL on the TFP of heavily polluting enterprises is not pronounced in the sample of small-scale enterprises; when the degree of financial slack is small, the effect of the EPTL on firms’ TFP is greater; the effect of the EPTL is greater when the enterprises are located in provincial capital and municipalities. (3) Meanwhile, we also find that promoting firm value and stimulating green innovation may be the potential mechanisms of the EPTL affecting firms’ TFP. This paper provides experience summary for the firms’ high-quality development under the background of government environmental governance.